Self-Reported and Performance-Based Outcome Measures Estimation Using Wearables After Unilateral Total Knee Arthroplasty - Youn, Ik-Hyun; Leutzinger, Todd; Youn, Jong-Hoon; Zeni, Joseph A.; Knarr, Brian A. (Frontiers in Sports and Active Living, 2020)
Total knee arthroplasty is a common surgical treatment to improve ambulatory function for individuals with end-stage osteoarthritis of the knee. Functional and self-reported measures are widely used to assess functional ability and impairment before and after the knee treatment. However, clinical assessments have limitations and often provide subjective and limited information. Seamless gait characteristic monitoring in the real-world condition is a viable alternative to address these limitations, but the effectiveness of using wearable sensors for knee treatment is unclear. The purpose of this study was to determine if inertial gait variables from wearable sensors effectively estimate the self-reported, performance, and isometric measure outcomes in individuals after unilateral total knee arthroplasty. Eighteen subjects at least six months post-surgery participated in the experiment. In one session, three tasks, including self-reported surveys, functional testing, and isometric tests were conducted. In another session, the participants’ gait patterns were measured during a one-minute walking test at their self-selected gait speed with two accelerometers worn above the lateral malleoli. Session order was inconsistent between subjects. Significant inertial gait variables were selected using stepwise regressions, and the contributions of different categories of inertial gait variables were examined using hierarchical regressions. Our results indicate inertial gait variables were efficient in predicting performance tests and questionnaires but not applicable in predicting isometric strength. The findings demonstrate that wearable sensor-based gait analysis can predict clinical measures in individuals after unilateral knee treatment.